RETRACTED: Developing a chatbot-based information system for employee interaction - Orlov Vasiliy; Tynchenko Vadim; Volneykina Ekaterina; Shutkina Elizaveta; Stupin Artem (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001